Towards Curative Therapy in Burkitt Lymphoma: The Role of Early African Studies in Demonstrating the Value of Combination Therapy and CNS Prophylaxis - Ian Magrath (Advances in Hematology)
This paper describes the treatment of Burkitt lymphoma (BL) from the time of its discovery in Africa up to the present. Pioneer investigators explored the value of chemotherapy since surgery and radiation were not effective modalities. Complete response was observed with many drugs used as single agents, but Ziegler and colleagues showed that patients resistant to one drug could achieve cure and potentially long-term survival with other drugs. Subsequently, a combination of cyclophosphamide (CTX), vincristine (VCR), and methotrexate (MTX) was shown to be active, but a survival advantage compared to CTX alone could not be demonstrated because effective CNS prophylactic therapy, in the form of intrathecal therapy, was not given. A recent re-evaluation of this regimen in Africa with multiple doses of intrathecal therapy compares favourably with recent studies of single agent CTX, and other drugs have been shown to be non-cross resistant. Optimal results for patients with extensive disease probably require 5 or 6 effective drugs along with intrathecal therapy, using MTX and Ara-C. In Africa, doses must be lower, because of limitations in supportive care, but in technically advanced countries cure rates in excess of 90% can be obtained. Rituximab may improve the results in some patient groups and allow less intensive therapy without a reduction in survival in others.